1960
DOI: 10.1152/ajplegacy.1960.198.5.934
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and rectification of muscle fiber membrane by tetrodotoxin

Abstract: The mode of action of tetrodotoxin on the frog muscle fiber membrane has been analyzed with the aid of intracellular microelectrodes. Tetrodotoxin of 10–7 concentration made the applied cathodal current ineffective in producing action potential, whereas the resting potential and resting membrane resistance underwent little or no change. With 10–8 tetrodotoxin the muscle fibers responded with the small action potentials at high critical depolarizations. These results can be explained on the basis of the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

1970
1970
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(56 citation statements)
references
References 0 publications
4
51
0
1
Order By: Relevance
“…The resting potential remained unchanged. These facts agree with the results on other materials (NAKAJIMA et al, 1962;NAKAMURA et al, 1963NAKAMURA et al, , 1965NARAHASHI et al, 1960NARAHASHI et al, , 1964. Figure 3 shows the action of TTX on the spontaneously produced slow potential and spikes.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The resting potential remained unchanged. These facts agree with the results on other materials (NAKAJIMA et al, 1962;NAKAMURA et al, 1963NAKAMURA et al, , 1965NARAHASHI et al, 1960NARAHASHI et al, , 1964. Figure 3 shows the action of TTX on the spontaneously produced slow potential and spikes.…”
supporting
confidence: 90%
“…Tetrodotoxin abolishes action potentials in various excitable cells such as the skeletal muscle fiber of frog (NARAHASHI et al, 1960;NAKAJIMA et al, 1962), the giant axons of squid (NAKAMURA et al, 1965) and lobster (NARAHASHI et al, 1964), and the electroplaque of electric eel (NAKAMURA et al, 1963). However, TTX has no effect on the action potential of the muscle fiber of barnacle (HAGIWA-RA and NAKA, 1964) or the synaptic potential in the endplate of frog muscle (FURU-KAWA et al, 1959).…”
Section: Discussionmentioning
confidence: 99%
“…We found that muscle responses during EFS were unchanged following addition of chagasic sera suggesting that the reduction in tone was not secondary to an alteration in neuronal activity. This evidence was strengthened by the observation that the effect was not prevented by pre-incubation of muscle preparations with the voltage-gated sodium channel blocker tetrodotoxin, which prevents action potential generation (Narahashi et al 1960;Kao 1964). Furthermore, we found that the effect was not dependent on production of nitric oxide, the principle neurotransmitter of inhibitory motor neurons, or mAChR activation.…”
Section: Significance and Interpretationssupporting
confidence: 55%
“…As these negative responses to phenylephrine were blocked by tetrodotoxin, phenylephrine appears to cause an excitation of parasympathetic nerve fibers. It is well known that tetrodotoxin blocks selectively the sodium carrier system of excitable tissue, particularly nerve fibers (15,16), and Hashimoto and Chiba (17) demonstrated that tetrodotoxin when injected into the sinus node artery blocks transmitter release caused by nerve excitation on the SA node area.…”
Section: Discussionmentioning
confidence: 99%